THE METHODS OF STUDY SELECTION OPTIONS FOR AN ENTERPRISE MODERNIZATION - Samkov, A.V. (Perm Federal Research Centre Journal, 2016)
Methods of preselection enterprise upgrade options based on international management standards for the early stages of project preparation are discussed. Examples of comparison of software products of the leading world manufacturers, their results and practical recommendations are presented.